Analisis Nilai-nilai Pendidikan Karakter dalam Kitab Akhlaku Lil Banin Jilid 1-2 - Wiratama, Rivaldi; Novidayanti, M.; Ilma, Fatkhul (Mitra PGMI: Jurnal Kependidikan MI, 2024)
This research aims to identify the values of character education contained in the book Akhlaku Lil Banin by Umar bin Ahmad Bardja volume one and volume two. The research method used is the literature review method, namely by analyzing deeply and systematically related to the contents of the book of Akhlaku Lil Banin as a primary source and other relevant scientific articles as secondary sources. The results of this study show that in the first volume of this book there is character education in the form of polite, honest, obedient, or religious, and responsible qualities, then in the second volume there is the value of character education in the form of religious qualities, filial piety to parents, caring for neighbors, and respecting teachers and friends.